2008
DOI: 10.1534/genetics.107.079707
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mixed-Model Approaches for Association Mapping

Abstract: Association-mapping methods promise to overcome the limitations of linkage-mapping methods. The main objectives of this study were to (i) evaluate various methods for association mapping in the autogamous species wheat using an empirical data set, (ii) determine a marker-based kinship matrix using a restricted maximum-likelihood (REML) estimate of the probability of two alleles at the same locus being identical in state but not identical by descent, and (iii) compare the results of association-mapping approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
229
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(234 citation statements)
references
References 34 publications
4
229
0
1
Order By: Relevance
“…In addition, the third criterion for selection of lines included a pre-evaluation for vernalization requirement, thus excluding winter types from the panel. In contrast to these results, Stich et al (2008) implemented GWAS in wheat and found that including P in the mixed model improved control of false positives relative to just including K. However, as pointed out in Stich et al (2008), inclusion of P in the mixed model had a large effect most likely because of the high levels of population structure that exists in wheat.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the third criterion for selection of lines included a pre-evaluation for vernalization requirement, thus excluding winter types from the panel. In contrast to these results, Stich et al (2008) implemented GWAS in wheat and found that including P in the mixed model improved control of false positives relative to just including K. However, as pointed out in Stich et al (2008), inclusion of P in the mixed model had a large effect most likely because of the high levels of population structure that exists in wheat.…”
Section: Discussionmentioning
confidence: 90%
“…Several statistical approaches for JLAM have been suggested based on linear (Yu et al, 2008;Liu et al, 2011) or linear mixed models (Stich et al, 2008). In addition, the QIPDT approach has been suggested (Stich et al, 2006), but the relationship between parents can better be exploited by using linear mixed models including a kinship matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Plant materials, phenotypic data and molecular markers To assess the performance of our method, we used three empirical data sets that were described in detail by Stich et al (2008) (winter wheat) and by Stich and Melchinger (2009) (sugar beet and rapeseed).…”
Section: Methodsmentioning
confidence: 99%
“…In the study of Stich et al (2008) the empirical type I error rates of association mapping approaches, which were based on adjusted entry means calculated by a two-step analysis, were only slightly higher than that of approaches in which the phenotypic data analysis and the association analysis were performed in one step (one-step analysis) (also see Mö hring and Piepho, 2009). We therefore calculated adjusted entry means (winter wheat and rapeseed) or entry means (sugar beet) in the first step (for more details, see Stich et al, 2008;Stich and Melchinger, 2009) for each entry under consideration.…”
Section: Statistical Analyses Phenotypic Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation